Ground cover classification of satellite imagery on parallel architectures - Liu, Bo (2008)
In this thesis, a detailed review is performed on some existed unsupervised classification algorithms, such as k-means, fuzzy k-means, ISODATA, Improved Splitting and Merging Clustering (ISMC) algorithm, and Mean-Shift algorithm. In particular, the ISMC algorithm and the Mean-Shift algorithm are analysed carefully here.